If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = x + -1 Reorder the terms: 5 + 3x = x + -1 Reorder the terms: 5 + 3x = -1 + x Solving 5 + 3x = -1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + 3x + -1x = -1 + x + -1x Combine like terms: 3x + -1x = 2x 5 + 2x = -1 + x + -1x Combine like terms: x + -1x = 0 5 + 2x = -1 + 0 5 + 2x = -1 Add '-5' to each side of the equation. 5 + -5 + 2x = -1 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = -1 + -5 2x = -1 + -5 Combine like terms: -1 + -5 = -6 2x = -6 Divide each side by '2'. x = -3 Simplifying x = -3
| 3(4+x)=x+6 | | -4u+2=-30 | | 2(2x+3)+x=3x+18 | | 3p-5=35 | | 1677633x+445277=4567(n+55264)+62698 | | 1350k=75 | | -6w+5t=11 | | 5a+7=-23 | | 3(-x+2)+x-1=-x-3 | | 5t-6w=11 | | -5x+1=-10 | | 32k=2000 | | -33=-15+-12 | | 3x+20+4x+5=8x+15 | | 32=2000 | | 3(2x-5)+4(x-2)=12 | | 5(3x+5)=17+12 | | 3x^2=2x+21 | | 53=16x-3 | | x+38=86-3x | | 55=3x+2+13x-3 | | 14=7p-9p | | 11x=-44 | | 16z+4x=y | | 4x^2+6=26 | | 52[72]= | | 0.5[2x+8]=x-4 | | 2x+b=c | | -6+3x=6 | | 3x^2-12x+45=0 | | x*2-25y*2=0 | | 7x^2+6x+1=0 |